Use of a Novel 5′‐Regioselective Phosphitylating Reagent for One‐Pot Synthesis of Nucleoside 5′‐Triphosphates from Unprotected Nucleosides. Issue 1 (1st March 2013) - Caton‐Williams, Julianne; Hoxhaj, Rudiona; Fiaz, Bilal; Huang, Zhen
Abstract: 5′‐Triphosphates are building blocks for enzymatic synthesis of DNA and RNA. This unit presents a protocol for convenient synthesis of 2′‐deoxyribo‐ and ribonucleoside 5′‐triphosphates (dNTPs and NTPs) from any natural or modified base. This one‐pot synthesis can also be employed to prepare triphosphate analogs with a sulfur or selenium atom in place of a non‐bridging oxygen atom of the α‐phosphate. These S‐ or Se‐modified dNTPs and NTPs can be used to prepare diastereomerically pure phosphorothioate or phosphoroselenoate nucleic acids. Even without extensive purification, the dNTPs or NTPs synthesized by this method are of high quality and can be used directly in DNA polymerization or RNA transcription. Synthesis and purification of the 5′‐triphosphates, as well as analysis and confirmation of natural and sulfur‐ or selenium‐modified nucleic acids, are described in this protocol unit. Curr. Protoc. Nucleic Acid Chem . 52:1.30.1‐1.30.21. © 2013 by John Wiley & Sons, Inc.